Design considerations for graded index fiber tip Fabry–Perot interferometers. (12th March 2021) - Riesen, Nicolas; Phillips, Nicholas; Nguyen, Linh V; Warren-Smith, Stephen C; Priest, Craig; Lancaster, David G
Abstract: An analysis is provided of fiber-optic Fabry–Perot interferometers designed and fabricated using collimating graded-index fiber (GIF) tips as an alternative to typical highly divergent standard single-mode fibers (SMFs). The collimated beam from the GIF tips allows for significantly longer etalons to be fabricated due to the increased collection efficiency when used either in reflection or transmission mode. We extend previous results, showing that GIF tips using coreless fiber segments can allow for up to four-fold increase in fringe visibility (FV) at 1550 nm compared with standard SMF Fabry–Perot etalons of the same length. The collimating GIF tips help lessen the FV vs cavity length trade-off typically observed in fiber-optic Fabry–Perot systems. We also explore the effects on FV improvement when using capillaries to align the fibres. This paper also provides easily accessible design guidelines and considerations for fabricating GIF based devices at 1550 nm.